Community Service at SDK Nita 1 on Integrated Environmental and Local Wisdom Education - El Puang, Desi Maria; Soludale, Anastasia Merdekawati Noralita; Ware, Klaudius; Owa, Maria Nelpi; Rina, Febriana (Abdi Masyarakat, 2025)
Learning at SDK Nita 1 still relies on textbooks without the development of contextual teaching materials, so that local wisdom is not optimally utilized in the learning process. In addition, waste management at the school has not been carried out properly because all waste is burned every morning, causing pollution and health risks for the school community. This community service activity aims to improve teachers' ability to develop teaching materials based on the local wisdom of Sikka Regency and to increase the awareness and skills of the school community in environmentally friendly waste management. The implementation methods include socialization, training, technology application, mentoring, evaluation, and program sustainability in two focus areas: teaching material development and waste management education. The results of the activity show a significant increase in competence and behavior. A total of 100% of teachers successfully developed teaching materials based on local wisdom using design technology (Canva), and all of them were able to manage the related learning administration. In terms of the environment, 75% of school members were able to sort organic, inorganic, paper, and hazardous waste; 75% were able to process organic waste into compost; 75% were able to make bricks from plastic waste; 85% were able to store inorganic waste suitable for sale at waste banks; and 80% were able to use compost for educational plants. Waste management facilities such as segregated trash bins, compost bins, and waste banks have also been successfully established as supporting infrastructure. Waste management facilities such as separate trash bins, compost bins, and waste banks were also successfully set up to support sustainability. These findings show that integrating local wisdom and environmental education into PkM can create more contextual learning and build a clean, healthy, and sustainable school culture.